PEMBULATAN TIMBANGAN PADA JASA PENGIRIMAN BARANG MENURUT KOMPILASI HUKUM EKONOMI SYARIAH DAN UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Faruq, M; Sukardi, Sukardi; Suhardiman, Suhardiman (Al-Aqad, 2022)
This research aims to analyze the practice of rounding the scales related to the delivery of goods from consumers where the rounding is carried out without notification. This research uses the legal method and is classified as a type of normative legal research-empiric with objects rounding the scales on freight forwarding services at PT. JNE Main Branch of Pontianak. The data source used by researchers to obtain the data - data needed in this study uses primary data and secondary data, primary legal material, and secondary which supports the analysis of rounding the scales on freight forwarding services at PT. JNE Main Branch of Pontianak. The technique used to collect data is a technical field. However, according to the research analysis results, it can be concluded that: 1) Rounding of scales at PT. JNE Main Branch of Pontianak is rounding up to the results of the scales if the weight of the item is less than 1 kg, the perch 1 kg if the weight of the item exceeds 1.3 kg then rounded 2 kg. 2) Rounding the scales carried out by this company is not following KHES article 295 and article 317. Whereas from Law Number 8 about Consumer Protection in the year 1999, contained in article 4 that the consumer has the right to obtain information and article 7 where the business actor is obliged to provide clear, correct information regarding the rounding he does. Keywords: Rounding Scales, KHES, Law No. 8 (1999)